Identifying potential inhibitors for wild-type EGFR tyrosine kinase through a cross-talk pathway strategy and an in-silico drug repurposing method - Dorra Abdelmalek; Kawther Bedchich; Fahmi Smaoui; Salim Kraiem; Mohamed Ali Mosrati; Mohamed Sami Aifa (PLoS ONE, 2026)
Wild-type epidermal growth factor receptor (EGFRwt) is commonly implicated in tumor growth, yet most of the approved EGFR-targeted therapies are against mutant receptor isoforms, and patients with EGFRwt-dependent cancers have limited treatment options. We herein explored the potential to inhibit EGFRwt with five top screened hits retrieved from Food and Drug Administration (FDA)-approved kinase inhibitors library, originally developed for MET-overexpressing cancers for potential drug repurposing approach. Induced-fit docking showed that all five molecules bound the ATP-binding pocket of EGFRwt, with compound D4 emerging as the top candidate due to key interactions with ASP855 (DFG motif) and MET793 (hinge region), underscoring its favorable engagement. To further assess this interaction, we then conducted 100 ns molecular dynamics (MD) simulations, confirming the structural stability of the EGFRwt–D4 complex, with stable root-mean-square deviation (RMSD) values and maintained secondary structure elements. Free energy of binding calculations using the Molecular Mechanics/Poisson–Boltzmann Surface Area (MM/PBSA) method supported these findings, with D4 showing the most favourable interaction, dominated by Van Der Waals and electrostatic contributions from key catalytic amino acid. Our research, with further experimental validation, could be helpful to support that certain MET inhibitors, especially D4, are promising competitive inhibitors of EGFRwt, offering potential for the development of new therapeutic strategies targeting EGFRwt-driven cancers.